Neural Measures Reveal a Fixed Item Limit in Subitizing - Ester, Edward F.; Drew, Trafton; Klee, Daniel; Vogel, Edward K.; Awh, Edward (The Journal of neuroscience, 2012)
For centuries, it has been known that humans can rapidly and accurately enumerate small sets of items, a process referred to as subitizing. However, there is still active debate regarding the mechanisms that mediate this ability. For example, some have argued that subitizing reflects the operation of a fixed-capacity individuation mechanism that enables concurrent access to a small number of items. However, others have argued that subitizing reflects the operation of a continuous numerical estimation mechanism whose precision varies with numerosity in a manner consistent with Weber's law. Critically, quantitative models based on either of these predictions can provide a reasonable description of subitizing performance, making it difficult to discriminate between these alternatives solely on the basis of subjects' behavioral performance. Here, we attempted to discriminate between fixed-capacity and continuous estimation models of subitizing using neural measures. In two experiments, we recorded EEGs while subjects performed a demanding subitizing task and examined set-size-dependent changes in a neurophysiological marker of visual selection (the N2pc event-related potential component) evoked by an array of to-be-enumerated items. In both experiments, N2pc amplitudes increased monotonically within the subitizing range before reaching an asymptotic limit at approximately three items. Moreover, inter-participant differences in the location of this asymptote were strongly predictive of behavioral estimates of subitizing span derived from a fixed-capacity model. Thus, neural activity linked with subitizing ability shows evidence of an early and discrete limit in the number of items that can be concurrently apprehended, supporting a fixed-capacity model of this process.